Increased Incidence of Obstructive Sleep Apnea in Hospitalized Children After Enterovirus Infection: A Nationwide Population-based Cohort Study. Issue 9 (September 2018) - Chen, Vincent Chin-Hung; Yang, Yao-Hsu; Kuo, Ting-Yu; Huang, Kuo-You; Huang, Yin-Cheng; Lee, Yena; McIntyre, Roger S.; Huang, Yu-Shu; Hsu, Chung-Yao
Abstract : Background: We report the first nationwide population-based cohort study using Taiwan's National Health Insurance Research Database on the association between enterovirus (EV) infection and the incidence of sleep disorders in a pediatric population. Methods: Two matched groups of children under 18 years of age were included in the analyses for nonapneic sleep disorder and obstructive sleep apnea (OSA). Among them, 316 subjects were diagnosed with OSA during the surveillance period, including 182 in the EV infection group and 134 in the non-EV infection group. Results: Hospitalization because of EV infection was associated with OSA after adjusting for age, sex, urbanization atopic disease and perinatal complications (adjusted hazard ratio: 1.62, 95% confidence interval: 1.18–2.21; P = 0.003). An additional factor significantly associated with sleep apnea was allergic rhinitis (hazard ratio: 4.82, 95% confidence interval: 3.45–6.72). Conclusions: Children with severe EV infection (ie, requiring hospitalization) carry a significantly higher risk of developing OSA, particularly in those with allergic rhinitis. As pediatric obstructive sleep apnea is a treatable sleep disorder, we emphasize regular follow-up and early detection in children with EV infection.